(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study was to analyze the relation between Quality of Life (QL) and alcohol consumption among students attending the Physical Education & Sports Course at a private faculty in the city of Campinas-SP, as well as to verify possible differences in the amount of alcohol consumption and QL between sexes. The sample was composed by 61 individuals with ages ranging from 18 to 50 years, being 30 males and 31 females, students of the Course of Physical Education & Sports. The AUDIT was used to measure their level of alcohol consumption and the WHOQOL-Bref questionnaire to evaluate QL. The test U was used to verify the possible differences between sexes in alcohol consumption and QL, and Spearman’s correlation to assess the relation between QL and alcohol consumption for those college students. The AUDIT analysis showed low indexes of alcohol consumption among students attending the Physical Education & Sports Course. Regarding sex, similar indexes were observed in alcohol consumption patterns with no evident significant differences. The QL results were satisfactory and men presented significantly better results than women in all WHOQOL-Bref domains, as well as for the overall QL (p <0,05). Concerning the relation between QL and alcohol consumption no significant correlation was observed between any of the WHOQOL-Bref domains and alcohol consumption results for the college students under study. It can be inferred that male and female students attending the Physical Education & Sports Course at that specific Institution under study possess similar alcohol consumption patterns with men presenting better results in QL than women. Taking into account that there was no relation between QL and alcohol consumption, studies evaluating different age groups and with a representative sample are necessary to explain that association.